Carbonylative Suzuki coupling reactions catalyzed by ONO pincer–type Pd(II) complexes using chloroform as a carbon monoxide surrogate. (3rd January 2020) - Layek, Samaresh; Agrahari, Bhumika; Ganguly, Rakesh; Das, Parthasarathi; Pathak, Devendra D.
Abstract : Benzoylhydrazone Schiff base–ligated three new ONO pincer–type palladium(II) complexes, [(PdL 1 (PPh3 )] (1 ), [(PdL 2 (PPh3 )] (2 ), and [(PdL 3 (PPh3 )] (3 ), were synthesized by the reaction of the respective ligand, N ‐(2‐hydroxybenzylidene)benzohydrazide (HL 1 ), N ‐(2‐hydroxy‐3‐methoxybenzylidene)benzohydrazide (HL 2 ), or N ‐(5‐bromo‐2‐hydroxybenzylidene) benzohydrazide (HL 3 ), with Pd(OAc)2 and PPh3 in methanol and isolated as air‐stable reddish‐orange crystalline solids in high yields (78%–83%). All three complexes were fully characterized by elemental analysis, Fourier‐transform infrared spectroscopy, UV–Visible, 1 H nuclear magnetic resonance (NMR), 13 C 1 H NMR, and 31 P 1 H NMR spectroscopic studies. The molecular structure of all three complexes was established unambiguously by single‐crystal X‐ray diffraction studies which revealed a distorted square planar geometry of all three complexes. The ONO pincer–type ligands occupied three coordination sites at the palladium, while the fourth site is occupied by the monodentate triphenylphosphine ligand. The catalytic potential of all three complexes was explored in the carbonylative Suzuki coupling of aryl bromides and iodides with arylboronic acids to yield biaryl ketones, using CHCl3 as the source of carbonyl. The reported protocol is convenient and safe as it obviates the use of carbon monoxide (CO) balloons or pressured CO reactors which are otherwise needed for the carbonylation reactions. The methodology has been successfully applied to the synthesis of two antineoplastic drugs, namely, phenstatin and naphthylphenstatin, in good yields (81% and 85%, respectively). Under the optimized reaction conditions, complex 2 exhibited the best catalytic activity in the carbonylative Suzuki couplings. The reported catalysts have wide reaction scope with good functional group tolerance. All catalysts could be retrieved from the reaction after completion and recycled up to three times with insignificant loss in the catalytic activity. Abstract : The synthesis and characterization of three new ONO‐pincer type Pd(II) complexes, [(PdL1(PPh3)], [(PdL2(PPh3)], and [(PdL3(PPh3)] is reported. All three complexes were fully characterized by Elemental analysis, FT‐IR, 1HNMR, 13C1H NMR and 31P1H NMR spectroscopic studies and the structures of all complexes are confirmed by single crystal X‐rays tudies. The catalytic potential of the new complexes is explored in the carbonylative Suzuki coupling of aryl bromides/iodides with arylboronic acids to yield biaryl ketones, using CHCl3 as the source of carbonyl.